Assessment of Energy Use and Carbon Dioxide Emissions in Tillage Systems for Cowpea Production in Derived Savanna Zone - Babajide S. Kosemani; Bamgboye A. Isaac; Ayoola A. Babalola (Jurnal Keteknikan Pertanian Tropis dan Biosistem)
Erratic global climate conditions endanger agricultural production's viability. Tailoring tillage practices to specific agro-ecological conditions is crucial for reducing energy use and carbon emissions. The objectives of this research were to investigate the energy consumption and carbon emissions of various tillage methods for cowpea production in the Savanah environment, as well as the impact of the tillage methods on cowpea bean yield. A field experiment was carried out using cowpea (Ife brown), and four tillage treatments were tested: minimum without stubble (M), minimum with stubble (Ms), conventional without stubble (Cw), and conventional with stubble (Cs). The experiment was designed as a randomised complete block with three replications. Fuel consumed by the different tillage systems were measured directly and converted to energy and emission using standard procedure. Significant (P < 0.05) differences were found between tillage methods in terms of specific fuel use, energy consumption, CO2 emissions, and bean production. The specific fuel consumption for M, Ms, CW and Cs were 39.38, 40.89, 42.01 and 98.70 L/ton, respectively. The specific energy consumptions were 2.61, 2.96, 4.17and 5.52GJ/ton, respectively. The specific CO2 emissions were 161.28, 182.45, 259.17 and 338.59 KgCO2/ton, respectively. In terms of energy usage, and CO2 emissions the minimum tillage method without stubble was the most efficient.